2018
DOI: 10.1021/acs.joc.8b00676
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Electrophilic Trifluoroethylthiolation with NaSO2CH2CF3

Abstract: Metal-free trifluoroethylthiolation with fluorinated sulfinate salt NaSOCHCF under reductive conditions has been developed. The strategy enables the installation of the SCHCF moiety efficiently to form a number of unexplored stable trifluoroethylthiolated heterocycles, arenes, and thiols, which have the potential to be a new series of fluorine-containing chemical entities for medicinal chemists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…It was found that 64 % yield of the product was achieved when 1.0 equiv. of TsCl was utilized (entries [5][6][7][8]. The effects of different solvents in the reaction were then investigated and cyclohexane was selected as the most suitable solvent for this transformation (entries 9-12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that 64 % yield of the product was achieved when 1.0 equiv. of TsCl was utilized (entries [5][6][7][8]. The effects of different solvents in the reaction were then investigated and cyclohexane was selected as the most suitable solvent for this transformation (entries 9-12).…”
Section: Resultsmentioning
confidence: 99%
“…[1] Especially heteroaromatic sulfides and their derivatives play significant roles in medicinal chemistry and drug development ( Figure 1). [2] Additionally, heteroaromatic sulfides can be further transformed into thiols, [3] sulfoxides, [4] sulfones, [5] and applied to cross-coupling reaction. [6] The formation of CÀ S bond has attracted extensive attention from chemists in recent ten years.…”
Section: Introductionmentioning
confidence: 99%
“…12 Yi and co-workers reported the synthesis of CF 3 CH 2 SO 2 Na first and used this reagent for trifluoroethylthiolation at the C-3 position of indoles in 2018. 13 On the basis of Yi's research, we tried to use the reagent to achieve trifluoroethylation of the C-2 position of indoles (Figure 2f). Herein, we reported a new method to synthesize CF 3 CH 2 SO 2 Na, which could be prepared simply from 2mercaptobenzothiazole and CF 3 CH 2 I on a large scale in 58% yield [eq 1].…”
mentioning
confidence: 94%
“…In the same year, Weng and co-workers developed a simple method for the synthesis of 2-(2,2,2-trifluoroethyl)-substituted indoles through a one-pot sequence (Figure e) . Yi and co-workers reported the synthesis of CF 3 CH 2 SO 2 Na first and used this reagent for trifluoroethylthiolation at the C-3 position of indoles in 2018 . On the basis of Yi’s research, we tried to use the reagent to achieve trifluoroethylation of the C-2 position of indoles (Figure f). …”
mentioning
confidence: 99%
“…Due to the masked effect and their high stability and being odorless, they have been widely used in the development of sulfides as sulfur sources . Inspired by these seminal works and our continuous research interests in fluorine-containing sodium salts, we decided to disclose a typical Bunte salt, sodium S -(fluoromethyl) sulfurothioate, that could be a potential monofluoro­methyl­thiolating reagent.…”
mentioning
confidence: 99%